2004
DOI: 10.1017/s0021859605004867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary algal docosahexaenoic acid oil supplementation on fatty acid deposition and gene expression in laying Leghorn hens

Abstract: SU MMARYThe purpose of the current study was to determine the effects of dietary docosahexaenoic acid (DHA) on fatty acid deposition in egg yolk and various tissues of laying Leghorn hens, and on the expression of hepatic lipogenesis-related transcription factors. There were three treatments with 10 Leghorn hens per treatment. Diets were based on maize-soybean meal (ME : 12 MJ/kg; CP : 171 g/kg ; Ca: 34 g/kg) supplemented with 0 (plus 20 g butter/kg), 5 g (plus 15 g butter/kg) or 20 g algal DHA oil/kg. The egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
4
18
1
Order By: Relevance
“…Interestingly, in laying hens, dietary DHA as DHA oil was not effective on the expression of SREBP-1 gene in liver [7,9]. It has been speculated that in the laying hens, the de novo lipogenesis in the liver is genetically high in order to generate yolk [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in laying hens, dietary DHA as DHA oil was not effective on the expression of SREBP-1 gene in liver [7,9]. It has been speculated that in the laying hens, the de novo lipogenesis in the liver is genetically high in order to generate yolk [7].…”
Section: Discussionmentioning
confidence: 99%
“…Reverse Transcription (RT) PCR was carried out using RT-PCR kit 7 containing RNA (5 µg), 1200 nM of gene specific primer and 2 µL diethylpyrocarbonate-treated water. The mixture was incubated at 65 ˚C for 5 min, then 2 µL buffer RT enzyme, 1 µl deoxy nucleoside triphosphate mix, and 400 U/µL of MMuLV Reverse Transcriptase 6 were added to the above mixture.…”
Section: Rna Isolation and Reverse Transcriptionmentioning
confidence: 99%
“…Diet supplementation of laying hens with different microalgae in order to increase DHA content in hen eggs has been successfully applied by many researchers (Cheng et al, 2004;Cachaldora et al, 2005;Rizzi et al, 2009). The fatty acid composition of the oil from Schizochytrium sp., apart from DHA, contains relatively high amount of DPA (16.32%, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no significant effects due to dietary treatments were observed (Table 9), so this was not pursued. Others have also failed to observe any significant effects of dietary ALA on mRNA expression in chicken breast muscle elongases and desaturases in broilers (Haug et al, 2014) or of dietary DHA on mRNA concentrations of the lipogenesis-related transcription factors SREBP1 and SREBP2 in the livers of laying hens (Cheng et al, 2004). Haug et al (2014) concluded that the concentration of VLC n-3 PUFAs may be regulated independently of changes in the expression of elongases and desaturases, and possibly more by substrate competition.…”
Section: Tablementioning
confidence: 99%